PERSEPSI MAHASISWA TERHADAP STRATEGI READING, QUESTIONING AND ANSWERING (RQA) DAN ARGUMENT-DRIVEN INQURY (ADI) - Amin, Astuti Muh. (Jurnal Pendidikan Biologi, 2016)
Individuals’ behaviors are regulated by how they perceive themselves and their surroundings. Learning that encourages students to be active will provide more effective environment to facilitate them to achieve predetermined learning objectives. It is very important to identify college students’ perception and investigate to what extent they can understand learning strategies that are being implemented. This research was a descriptive quantitative research which involved 142 biology education students. Two questionnaires were distributed to obtain students’ perception on the implementation of Reading Questioning and Answering (RQA) and Argument Driven Inqury (ADI) learning strategies. As to collect more data, observation and interviews were also conducted. Research findings indicate that (1) 38,32% of the students have ever heard about RQA, but only 18,60 of them have experienced learning biology with RQA;  (2) around 24,26% of the students are quite familiar with ADI, however, only 9,45% have been taught using the strategy.